Self-healing polymeric materials for potential dental application / Sonja Then - Then, Sonja (2011)
Poly(urea-formaldehyde) (PUF) microcapsules that enclose dicyclopentadiene (DCPD) were successfully prepared by in situ polymerization. The effect of diverse process parameters and concentrations of ingredients on the product yield and quality was investigated. After optimizing the procedure high yields of microcapsules were obtained (up to 89%) which appeared in the form of a free-flowing white powder. The morphology of the microcapsules was observed by digital microscopy, optical microscopy (OM), and field emission gun scanning electron microscopy (FESEM). FTIR and 1H-NMR were employed to analyze the chemical structure and content of the core material. The thermal properties were characterized utilizing DSC and TGA. The microcapsules could be incorporated into another polymeric host material. In the event the host material cracks due to excessive stress or strong impact, the microcapsules would rupture to release the DCPD, which could polymerize to repair the crack, thus autonomously heal the material.